Thermal characteristics of hybrid Nanofluid (Cu-Al2O3) flow through Darcy porous medium with chemical effects via numerical successive over relaxation technique - Assmaa Abd-Elmonem; Qammar Rubbab; Hakim AL. Garalleh; Fazeelat Rehman; Muhammad Amjad; Fayza Abdel Aziz ElSeabee; Nesreen Sirelkhtam Elmki Abdalla; Wasim Jamshed; Syed M. Hussain; Hijaz Ahmad (Case Studies in Thermal Engineering)
The flow of fluids through porous media is commonly described using the Darcy model, therefore investigating hybrid nanofluids in this setting is rather new. The present work offers insightful information on how the hybrid nanofluids behave and function in porous medium. The study's conclusions may have an impact on a lot of different engineering applications like filtration systems, chemical reactors, and environmental engineering. The study concentrates on a hybrid nanofluid which consists of Cu and Al₂O₃ nanoparticles. The metallic nanoparticles such as copper have high thermal conductivity and non-metallic nanoparticles such as aluminum oxide are chemically stable and has high thermal resistance. This is the reason that the combination Cu-Al₂O₃ is believed to give better heat transfer composite than using individual nanofluids. By employing proper similarity transformation, the governing PDEs are turned into ODEs. To discretize these ODEs, the central finite difference method is used first. Then the successive over relaxation technique is utilized to numerically solve the nonlinear equations. The findings are summarized in a graphical and tabular format. The impacts of several controlling parameters such as porosity, suction, Schmidt number and volume fraction on flow pattern, thermal properties, and concentration are investigated and discussed. The streamwise and normal velocity profiles fall and those of concentration and temperature rise with increase in the values of the porosity parameter.